2008
DOI: 10.1196/annals.1454.015
|View full text |Cite
|
Sign up to set email alerts
|

Domestic Fuels, Indoor Air Pollution, and Children's Health

Abstract: Reliance on solid biomass fuel for cooking and heating exposes many children of developing countries to high levels of indoor air pollution. This study investigates the association between household use of biomass fuels for cooking and prevalence of respiratory symptoms and diseases among children in rural India. The air-quality parameters (CO, CO(2), NO, NO(2), SO(2), O(3), suspended particulate matter (SPM), including temperature and relative humidity) were investigated using a YES-Plus multigas air-quality … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
52
1
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(58 citation statements)
references
References 17 publications
4
52
1
1
Order By: Relevance
“…Airborne concentrations of these pollutants were significantly higher in biomass-fuel-users' than fossil-fuel-users' kitchens at different measured times, which is consistent with the findings of other studies [23][24][25][26]. Considering the seasonal variation, we found a significant difference in the levels of dust particles and CO between winter and summer.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Airborne concentrations of these pollutants were significantly higher in biomass-fuel-users' than fossil-fuel-users' kitchens at different measured times, which is consistent with the findings of other studies [23][24][25][26]. Considering the seasonal variation, we found a significant difference in the levels of dust particles and CO between winter and summer.…”
Section: Discussionsupporting
confidence: 91%
“…Other studies revealed the association of exposure to indoor VOCs with respiratory diseases and symptoms [33,34]. Some other studies also demonstrated a positive relationship between air pollution from biomass combustion and child health [23,24,35,36]. In this study, although in both winter and summer there were differences in pollution levels with different fuel types, we noted no such differences in the occurrence of respiratory symptoms either in winter or summer.…”
Section: Discussionsupporting
confidence: 54%
“…4-5.3). Some other studies also demonstrated a positive relationship between air pollution from biomass combustion and child health [26][27][28]. In our study, we found that the levels of most of the indoor air pollutants were higher in urban area but that the occurrences of respiratory symptoms were higher in rural area.…”
Section: Discussionsupporting
confidence: 74%
“…Interestingly, power plant (19 Gg/yr) has shown lower emissions compared to emissions resulting from cultural places. Residential bioand fossil fuel use has shown many folds higher emission estimation of OC compared to the present study due to profuse consumption of conventional household cooking fuels in India (Ramakrishna et al, 1989;Smith, 1996;Taneja et al, 2008;Padhi and Padhy, 2008). In contrast to OC emission estimation, EC has shown significant annual emissions from cultural and ritual activities compared to that from transport sector.…”
Section: Annual Emission Budgetcontrasting
confidence: 46%